Genetic diversity and evolution of the human leptin locus tetranucleotide repeat - Moffett, Susan (2002)
To better understand the evolutionary history of the gene region containing the multifunctional adipose tissue hormone leptin, we genotyped 1,957 individuals from 12 world populations for a highly variable tetranucleotide repeat polymorphism located 476 bp 3′ of exon 3 of the leptin gene. Common alleles shared among populations, alleles specific to geographically defined populations, and the homologous alleles in the common and pygmy chimpanzee, the gorilla and the orangutan, were sequenced to define the allelic variation at the nucleotide level. These data reveal a common set of alleles shared among world populations, presumed to have arisen from a great ape ancestral allele prior to the divergence of the major geographical subdivisions of the human population, a subset of alleles specific to populations of African ancestry and a second set of alleles that arose by tandem duplication of the core repeat unit following the separation of African and non-African populations. These findings emphasize the complex evolutionary history of this locus and raise cautions about the pooling of alleles at this locus in association studies.